Strategy of Sustainable Entrepreneurship Development as an Effort to Create a Tourism-Based Economy in Coastal Communities on Kera Nepa Beach, Sampang Regency - Zainal Abidin; Arie Wahyu Prananta; Hapsari Puspita Rini (Postgraduate, University of Mataram, 2024)
This research aims to examine the potential development of a tourism-based creative economy in coastal communities on Kera Nepa Beach, Sampang Regency. This study describes the use of the marketing mix, namely Product, Price, Place, Promotion, and People, as an effort to create economic lean in coastal communities, especially on the north coast of Kera Nepa, Sampang Regency, Madura. This study used a descriptive qualitative method. Data was obtained from observation, interviews, and FGD using SWOT analysis techniques. The results obtained show that the economic development of Nepa Tourism Beach experienced less good development at the end of this period compared to several other tourist beaches in Sampang Regency which tended to increase. Researchers also found the need for a business strategy by diversifying products, namely changing market share by combining it with product changes. And it is necessary to increase the number of tourist visits to the area. Apart from that, it can also empower all existing resources around tourist attractions, both in terms of human resources and existing facilities. Researchers also found the influence of social, economic, cultural, and environmental impacts on local communities which had an impact on the weak entrepreneurial spirit